2021
DOI: 10.1021/acsomega.0c04033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigations of Growth of Anisotropic Nanostructures in Reverse Micelles

Abstract: Tailoring the characteristics of anisotropic nanostructures like size, morphology, aspect ratio, and size dispersity is of extreme importance due to the unique and tunable properties including catalytic, optical, photocatalytic, magnetic, photochemical, electrochemical, photoelectrochemical, and several other physical properties. The reverse microemulsion (RM) method offers a useful soft-template and low-temperature procedure that, by variation of experimental conditions and nature of reagents, has proved to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…Fatty acids can react with the base (K 2 CO 3 ), generating corresponding potassium salts, which have improved solubility in fats and can act as shuttle bases or phase transfer catalysts. Amphiphiles can form reversed micelles that have been shown to act as microreactors for Pd-catalyzed transformations . Accordingly, we set a series of control experiments to investigate the effect of various commercially available natural amphiphiles (50 mg) on the reaction in rapeseed oil (2 mL) from Sigma-Aldrich (Chart ).…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids can react with the base (K 2 CO 3 ), generating corresponding potassium salts, which have improved solubility in fats and can act as shuttle bases or phase transfer catalysts. Amphiphiles can form reversed micelles that have been shown to act as microreactors for Pd-catalyzed transformations . Accordingly, we set a series of control experiments to investigate the effect of various commercially available natural amphiphiles (50 mg) on the reaction in rapeseed oil (2 mL) from Sigma-Aldrich (Chart ).…”
Section: Resultsmentioning
confidence: 99%
“…Evolution of Dielectric Relaxations during the Synthesis Processes. The synthesis of silica NPs in reverse MEs has been extensively investigated, 8 and it has been found that a great number of factors can influence the synthesis process, such as water:surfactant molar ratio R, the cosurfactant:surfactant ratio, and the water:TEOS ratio. In addition to these structural factors, many nonstructural factors can affect the synthesis process, as well, for example, synthesis time, 5 reaction products, 7 and interdroplet interaction.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This situation has encouraged a great number of mechanistic studies of NP synthesis processes alongside the ME-based NP synthesis works. 8,9 Recently, in situ mechanistic studies by means of timeresolved techniques have demonstrated superiority in giving indepth insights into the dynamic nature of NP formation in ME-based synthesis. 10−18 In such studies, the evolution profiles of designated system properties provided by timeresolved techniques can directly mirror the dynamic synthesis processes in real time, through correlations of the designated properties with the structural and compositional features of the synthesis system in one aspect or another.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fabrication methods have been reported to prepare spinel manganese ferrite nanocrystals, including the sol-gel method (Banalata et al, 2014), coprecipitation (Irfán et al, 2012), synthesis in reverse micelles (Das et al, 2021) and the hydrothermal method (Mebdir and Sadiyha, 2019). Each method of ferrite obtaining has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%